The identification of tumor-infiltrating lymphocytes in patients with stomach cancer - Gulnoz G. Khakimova (IP Habib O.N., 2021)
Background. Stomach cancer (SC) is the 6th most common neoplasm among cancers (1 033 701 cases; 5.7%) and the 3rd most deadly cancer worldwide for men and women (782 685 deaths, 8.2%). SC therapy is a complex treatment associated with surgery, adjuvant chemotherapy, targeted therapy and immunotherapy with checkpoint inhibitors, nowadays. Despite the fact that the SC understanding has significantly increased within recent years, the prognosis still remains poor. In addition, very often the patients with the same stage of SC according to the international TNM classification of malignant tumors have different overall survival. Therefore, in order to improve survival rates, is necessary to understand the mechanisms of disease progression and to find new effective predictive factors. Besides many SC predictive factors, such as clinical and morphological characteristics (Lauren histologic type of tumor, degree of differentiation), biomarkers, deficient mismatch repair (dMMR), we have also revealed the positive correlation between the degree of tumor infiltration of tumor-infiltrating lymphocytes (TILs), especially with the spatial location of cell types (intratumoral or stromal cells), and the survival indicators of the patients with malignant neoplasms, recently. Moreover, TILs are the most significant predictive factors in patient survival rates than the TNM classification. At the same time, TILs predictive role in SC is still not clearly defined. Thus, the understanding of the degree of tumor infiltration of TILs depending on the spatial location would allow to determine the predictive significance, as well as to determine the direction of the immune reactions generating in patients with SC at the tissue level, depending on the risk and probability of progression.